Spiritual Happiness: A Phenomenological Study of the Congregation Members of the Pengajian Tauhid in Medan City - Mhd.Fajar Fadhillah; Syukri Syukri; Endang Ekowati (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to uncover the subjective experience of spiritual happiness among members of the Pengajian Tauhid at Jalan Suluh, Gang Sabir No. 2, Medan City. The research focuses exclusively on participants’ lived experiences derived from tauhid teachings as conveyed through lectures by the preacher (mualim). Employing Interpretative Phenomenological Analysis (IPA), the study explores the lived experience of both long-standing senior members and younger participants, each bringing distinct life challenges. Data were collected through participant observation and in-depth interviews with purposively selected key informants who differed in their duration of involvement in the study circle.vFindings reveal four superordinate themes that constitute their spiritual happiness: (1) inner tranquility, (2) emotional stability, (3) discovery of life direction, and (4) the role of the majelis as a protective social identity fortress against negative peer influences. These experiential elements mutually reinforce one another, producing a holistic lived experience. Participants describe spiritual happiness as a profound sense of peace accompanied by a firm conviction that Allah will always provide a “way out” from every life difficulty.vThe study concludes that tauhid-centred religious study circles can serve as powerful spaces for cultivating spiritual well-being, offering an authentic expression of life’s meaning rooted in Allah that effectively alleviates existential anxiety, fortifies the self against harmful influences, and enables adaptive emotional self-regulation in the face of modern existential challenges.